Akt confers cisplatin chemoresistance in human gynecological carcinoma cells by modulating PPM1D stability. Issue 11 (23rd August 2014) - Ali, Ahmed Y.; Kim, Ji‐Young; Pelletier, Jean‐François; Vanderhyden, Barbara C.; Bachvarov, Dimcho R.; Tsang, Benjamin K.
<x xml:space="preserve">Abstract</x> Ovarian cancer (OVCA) and cervical cancer (CECA) are lethal gynecological malignancies. Cisplatin (CDDP) and platinum derivatives are first line chemotherapeutics and their resistance impedes successful treatment. Understanding the molecular dysregulation underlying chemoresistance is important in developing rational therapeutic strategies. We have established that Protein Phosphatase Magnesium‐dependent 1 D (PPM1D) confers CDDP resistance in gynecological cancer cells by deactivating p53. However, whether CDDP regulates intra‐cellular PPM1D localization and whether this regulation is different between chemosensitive and chemoresistant cancer cells is unknown. Moreover, whether Akt regulates PPM1D in the context of CDDP resistance has not been studied. To illustrate the role of PPM1D in gynecological cancer cell chemoresistance and its regulation by Akt we have demonstrated that: (a) CDDP induced PPM1D down‐regulation through proteasomal degradation in sensitive CECA cells; (b) CDDP induced PPM1D nuclear localization in resistant CECA cells, and nuclear exclusion in sensitive CECA cells and OVCA xenografts; (c) Over‐expression of active Akt in sensitive CECA cells stabilized PPM1D content through inhibition of CDDP‐induced PPM1D down‐regulation; (d) Inhibition of Akt activity in resistant OVCA cells leads to decreased PPM1D stability and CDDP‐induced down‐regulation in resistant CECA cells; and (e) PPM1D is highly expressed in human ovarian tumor subtypes and in a tissue microarray panel of human ovarian tumors. In conclusion, we have established that PPM1D plays an important role in promoting CDDP resistance and as a novel downstream target of Akt, PPM1D mediates its action in conferring CDDP resistance in gynecological cancer cells. © 2014 The Authors. Molecular Carcinogenesis published by Wiley Periodicals, Inc.